1969
DOI: 10.2134/agronj1969.00021962006100020014x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Aluminum Tolerance of Winter Barley Varieties and Selections in Associated Greenhouse and Field Experiments1

Abstract: Thirty cultivars and experimental strains of winter barley (Hordeum vulgare) were grown on acid, aluminum‐toxic soils treated with two rates of lime in greenhouse tests and three rates in field tests. The objectives were to determine if greenhouse tests could be used for certain phases of breeding for Al‐tolerant barley varieties and to find possible new sources of Al‐tolerant germ plasm. Dry‐weight yields of top and root growth were determined after 7 weeks in the greenhouse. Grain yields were determined from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 8 publications
1
22
0
3
Order By: Relevance
“…Al toxicity inhibits root cell division and elongation, thus reducing water and nutrient uptake, consequently resulting in poorer plant growth and yield (Alam, 1981;Clarkson, 1966;Foy, 1983;Foy et al, 1967;Gauthier, 1953;Reid et al, 1969;1971). Relative shoot and root dry weights in tolerant barley cultivars were two-fold and three-fold respectively compared to susceptible cultivars (Foy, 1996).…”
Section: Effect Of Al Toxicity On Plant Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Al toxicity inhibits root cell division and elongation, thus reducing water and nutrient uptake, consequently resulting in poorer plant growth and yield (Alam, 1981;Clarkson, 1966;Foy, 1983;Foy et al, 1967;Gauthier, 1953;Reid et al, 1969;1971). Relative shoot and root dry weights in tolerant barley cultivars were two-fold and three-fold respectively compared to susceptible cultivars (Foy, 1996).…”
Section: Effect Of Al Toxicity On Plant Growth and Developmentmentioning
confidence: 99%
“…A wide range of genetic variation for Al tolerance exists in barley (Reid et al, 1969) and has been exploited to develop varieties with increased Al tolerance (Foy et al, 1965). In Australia, some breeding lines outperformed significantly better on acid soils than Al sensitive lines (Oram, 1983) and have been released for commercial cultivation on acid soils, for example Brindabella, Yambla, and Tulla.…”
Section: Genotypic Difference In Al Tolerancementioning
confidence: 99%
“…Assim, a Bragg tem a cultivar Jackson, como pai tolerante; a EMGOPA-302 e EMGOPA-304 têm a cultivar Mandarin, proveniente da China, tolerante (Armiger et al, 1968); a BR-13 tem a Bragg como pai tolerante, em retrocruzamento por quatro vezes. Linhas derivadas de retrocruzamentos, desenvolvidas sem seleção para tolerân-cia ao Al, tiveram o mesmo comportamento de tolerância quanto ao pai recorrente (Reid et al, 1969). A FT-1, proveniente de seleção em Sant'Ana, linhairmã de Lee, tolerante (Armiger et al, 1968;Sartain & Kamprath, 1978); e a Planalto, proveniente de Hood, que é tolerante (Sartain & Kamprath, 1978).…”
Section: Avaliação De Cultivares E Linhagens Brasileiras De Sojaunclassified
“…Chronic exposure to cadmium in humans has several toxic effects, such as high H + .The primary response to Al stress in plants occurs in roots, as reduced elongation at the tip, followed by swelling and distortion of differentiated cells, as well as root discoloration [8] Within meristematic and root cap cells, Al toxicity is associated with an increased vacuolation and turnover of starch grains, as well as disruption of dictyosomes and their secretory function. Al toxicity inhibits root cell division and elongation, thus reducing water and nutrient uptake, consequently resulting in poorer plant growth and yield [9,10,11]. Al toxicity also limits both rooting depth and degree of root branching demonstrated that there are two responses to Al: an initial acute inhibition of growth that is followed by a later chronic Al effect on root growth.…”
Section: Introductionmentioning
confidence: 99%